(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Over the past few years, euthanasia and physician assisted suicide have become prominent public issues in many countries. Several countries or regions of countries have debated legislation on euthanasia and / or physician assisted suicide. Although there is growing public acceptance of physician-assisted deaths all over the world; many professional organizations remain opposed to it. Most of the debates on the issue are usually framed, as issues of morality while many basic empirical questions remain unanswered. For example, how many patients actually make these requests? Would improved treatment of pain lead fewer patients to make these requests? How do physicians respond to these requests? To what extent these practices occur? etc. Can internationalization of the euthanasia debate help to resolve these issues and build the consensus, and can International Human Rights Law provide an adequate basis for such a debate? This paper attempts to examine these questions. Key Words: End of life decisions, Physician-assisted deaths, Physician-assisted suicides, Euthanasia